Purification and Characterization of Protease From Bacillus sp. TBRSN- 1 - Sebastian Margino; J. Jumi'ati; N. Ngadiman (Indonesian Journal of Biotechnology, 2013)
Potato Cyst Nematode (PCN), Globodera rostochiensis, is one of the important potato’s pests and causedeconomic looses up to 70% in the several centrals of potato plantations in Indonesia. PCN’s shell componentof egg shell containing chitin (inner layer) and viteline/ protein (outer layer). The purpose of this researchwas to purify of protease Bacillus sp. TBRSN-1, isolate from tomato’s rhizosfer in Yogyakarta province. Thepurifi ed protease could be used for cutting the life cycle of PCN. Results showed that Bacillus sp. TBRSN-1could produce extracellular protease and purifi cation using DEAE-cellulose ion-exchange chromatographyand Sephacryl S-300 gel fi ltration chromatography resulted in specifi c activity 4.31 fold and 1.68% recovery.Analysing using SDS-PAGE 12.5% and molecular weight 48.1 kDa. Km and Vmax values of the protease forcasein substrate were 7.83 mg/ml and 4.03 μg/h, respectively. The optimum activity at the temperature30oC and pH 7.0. Keywords : protease, purifi cation, indigenous Bacillus sp. TBRSN-1